Podoba : Insnov. - Moderna Galerija, Ljubljana (Ljubljana : Moderna Galerija, 1991)
Bernard, Emerik ; Bernik, Janez ; Gnamus, Gustav ; Gruden, France ; Gvardjancic, Herman ; Hocevar, Zoran ; Jemec, Andrej ; ertc.
Podoba Insnov, Moderna Galerija, Ljubljana, 14.2. - 31.3.1991
boek